Modified Versions of AM‐4 for the Aqueous Phase Isomerization of Aldo‐Saccharides. Issue 17 (14th April 2020) - Antunes, Margarida M.; Fernandes, Auguste; Ribeiro, M. Filipa; Lin, Zhi; Valente, Anabela A.
Abstract : The isomerization of aldo‐saccharides to keto‐saccharides is an important transformation in biomass conversion processes. The use of eco‐friendly heterogeneous catalysts for these reactions is most attractive, albeit good catalytic stability continues a challenge. The as‐synthesized Aveiro‐Manchester material number 4 (AM‐4, Na3 (Na, H)Ti2 O2 [Si2 O6 ]2, 2H2 O) possessed isomerization activity, but limited stability. This versatile precursor material was modified to meet superior performances in the base‐catalyzed isomerization of the monosaccharides d ‐glucose and d ‐xylose, and the disaccharide d ‐cellobiose, at 100 °C. Different alkali and alkaline‐earth metals were introduced into AM‐4, which influenced the catalytic properties. The Mg‐containing material was the most stable, leading to 27 % fructose yield from d ‐glucose, 41 % cellobiulose from d ‐cellobiose and 39 % xylulose from d ‐xylose isomerization, at 2 h reaction. Abstract : The titanosilicate Aveiro‐Manchester material number 4, AM‐4, has a unique layered structure and ion exchange ability. Post‐synthesis introduction of K, Ca, or Mg in AM‐4 led to active catalysts for the aqueous phase isomerization of aldo‐saccharides to keto‐saccharides: Mg‐AM‐4 was the most stable, leading to 27 % fructose yield from d ‐glucose, 41 % cellobiulose from d ‐cellobiose, and 39 % xylulose from d ‐xylose isomerization, at 100 °C, in 2 h.